95.4k views
2 votes
What is the difference between (Picture 1) and (picture 2)? A. 0 B. 2 C. 5 D. 6

What is the difference between (Picture 1) and (picture 2)? A. 0 B. 2 C. 5 D. 6-example-1
What is the difference between (Picture 1) and (picture 2)? A. 0 B. 2 C. 5 D. 6-example-1
What is the difference between (Picture 1) and (picture 2)? A. 0 B. 2 C. 5 D. 6-example-2

1 Answer

0 votes

Answer:

The difference between the picture is 0 , option A .

Explanation:

Given two figures as :

In figure A

The expression is 1 + 3 n , where n lies from 0 to 4

So , let f (n) = 1 + 3 n

Or,f ( n ) = 1 + 3 ×0 = 1 + 0 = 1

f ( 1 ) = 1 + 3 ×1 = 1+ 3 = 4

f ( 2 ) = 1 + 3 ×2 = 1+ 6 = 7

f ( 3 ) = 1 + 3 ×3 = 1+ 9 = 10

f ( 4 ) = 1 + 3 ×4 = 1+ 12 = 13

so, summation of ( 1 + 3 n ) from n = 0 to 4 = 1 + 4 + 7 + 10 + 13 = 35

In figure B

The expression is 3 i - 5 , where i lies from 2 to 6

So , let g (i) = 3 i - 5

Or,g ( 2 ) = 3 ×2 - 5 = 6 - 5 = 1

g ( 3 ) = 3 ×3 - 5 = 9 - 5 = 4

g ( 4 ) = 3 ×4 - 5 = 12 - 5 = 7

f ( 5 ) = 3 ×5 - 5 = 15 - 5 = 10

f ( 6 ) = 3 ×6 - 5 = 18 - 5 = 13

so, summation of ( 3 i - 5 ) from i = 2 to 6 = 1 + 4 + 7 + 10 + 13 = 35

So, The difference between the summation of functions f(n) - g(i) is

f(n) - g(i) = 35 - 35

I.e f(n) - g(i) = 0

Hence The difference between the picture is 0 , option A . Answer

User Rejinderi
by
5.7k points